2015
DOI: 10.1007/s11274-015-1886-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of roxarsone by a bacterial community of underground water and its toxic impact

Abstract: Roxarsone is included in chicken food as anticoccidial and mainly excreted unchanged in faeces. Microorganisms biotransform roxarsone into toxic compounds that leach and contaminate underground waters used for human consumption. This study evaluated roxarsone biotransformation by underground water microorganisms and the toxicity of the resulting compounds. Underground water from an agricultural field was used to prepare microcosms, containing 0.05 mM roxarsone, and cultured under aerobic or anaerobic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The enhanced toxicity was attributed to the improved membrane permeability of the inorganic arsenicals in the photodegradates of roxarsone . In the study of Mafla (2015), it was also confirmed that untransformed roxarsone was not a toxic product for eukaryotic or prokaryotic cells, and the toxicity was caused by the consequence of roxarsone biodegradation. Therefore, in this study, the inhibition of some soil bacteria might not occur as a result of roxarsone but rather from the arsenic compounds released by roxarsone degradation.…”
Section: Sequencing and Classificationmentioning
confidence: 82%
“…The enhanced toxicity was attributed to the improved membrane permeability of the inorganic arsenicals in the photodegradates of roxarsone . In the study of Mafla (2015), it was also confirmed that untransformed roxarsone was not a toxic product for eukaryotic or prokaryotic cells, and the toxicity was caused by the consequence of roxarsone biodegradation. Therefore, in this study, the inhibition of some soil bacteria might not occur as a result of roxarsone but rather from the arsenic compounds released by roxarsone degradation.…”
Section: Sequencing and Classificationmentioning
confidence: 82%
“…Measuring the half‐maximal inhibitory and half‐maximal effective concentrations of the As(V)‐ and As(III)‐bearing photodegradates of ROX exhibited 10‐fold higher toxicity than ROX itself, which was attributed to the improved membrane permeability of the inorganic arsenicals (Zhang, Xu, Han, Sun, & Yang, ). The toxicity for eukaryotic or prokaryotic cells is primarily caused by ROX biodegradation by microorganisms (Mafla et al, ). Therefore, in the present study, the inhibition of some soil bacteria might be from the arsenic compounds released following ROX degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation can occur under both aerobic and anaerobic conditions (Cortinas et al, ; Guzmán‐Fierro et al, ; Mafla et al, ; Stolz et al, ), and the rate of degradation is related to the initial ROX concentration in soil (Liu, Zhang, Li, Wen, et al, ). Degradation is faster in anaerobic conditions than in aerobic conditions, with ROX being completely degraded after 48 hr of dark anaerobic incubation, while only 79.9% and 94.5% were degraded after 288 hr of dark aerobic and light aerobic incubation, respectively (Liu, Zhang, Li, Wen, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Total DNA of each sample was amplified using 16S rRNA universal primers EUB 9-27 and EUB 1542 (Guzmán-Fierro et al 2015) [12]. Nested PCR was performed using the primer pair 341f and 534r with a GC clamp (CGCCC GCCGC GCGCG GCGGG CGGGG CGGGG GCACG GG GGG) according to Mafla et al [13]. DGGE was done using a DGGE 1001 system (C.B.S.…”
Section: Polymerase Chain Reaction (Pcr)-denaturing Gradient Gel Elecmentioning
confidence: 99%